HUBUNGAN KECEMASAN DAN KEPATUHAN KELUARGA PASIEN TERHADAP PENCEGAHAN PENULARAN COVID-19 - Deddy Sepadha Putra Sagala; Hamonangan Damanik; Sarida Surya Manurung; Erika Zai (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2023)
CoronaVirus (COVID-19) is a pandemic case since March 11, 2020. COVID-19 is a disease caused by CoronaVirus.CoronaVirus (CoV) is part of a family of viruses that cause illness ranging from the flu to more severe diseases such as Middle East Respiratory Syndrome (MERS-CoV) and Severe Acute Respiratory Syndrome (SARS-CoV). Globally confirmed on May 29, 2020 is 5,657,529 people and deaths are 356,254 in 216 countries. This study aims to determine the relationship between anxiety and patient family compliance with the transmission of Covid-19. This research is a quantitative research using a correlational design with the type of research design (cross sectional). The population in this study is the sum of the entire family of patients who visited the General Hospital Imelda Workers Indonesia Medan from July-August and the sample of this study was 97 respondents using purposive sampling method. Anxiety data collection used the Hamillion Rating Scale For Anxiety (HARS) questionnaire while for complaince data collecction used the 2022 Central Bureau Of Statistics questionnaire and analysis with Spearmen's test. The results showed that the relationship between anxiety and patient's family adherence to Covid-19 transmission was obtained with p value 0.002 <0.005 there was a relationship. Based on the results of this study, the more anxious, the more obedient in implementing health protocols.